Evaluation of Coconut Oilcake Carbon as Absorbent for Nickel Ion: Equilibrium and Kinetic Studies - Hema, M.; Srinivasan, K. (Asian Journal of Chemistry, 2010)
The adsorption behaviour of coconut oilcake activated carbon (COCAC) for nickel ion removal from wastewater has been investigated, as a function of appropriate equilibrium time, amount of adsorbent, concentration of adsorbate and pH using a batch system. The efficiency of COCAC was compared with commercial activated carbon (CAC). Studies showed that pH of wastewater affected nickel adsorption because of removal efficiency increased with increasing solution pH but after 5, the removal efficiency remains constant. The adsorption of Ni(II) was found to be maximum for COCAC (96.83 %) than CAC (74.8 %), at pH 7, contact time 30 min and initial Ni(II) concentration of 63 mg/L. The adsorption data fit well with Temkin isotherm model, the adsorption capacity ‘b’ calculated from the Langmuir isotherm was 555.56 and 30.77 mg/g for COCAC and CAC, respectively. The Freundlich constant Nf indicates beneficial adsorption. Kinetic studies show better applicability of second-order-kinetic model. Desorption studies were performed with dilute hydrochloric acid. Quantitative recovery of the metal ion is possible. The mechanism of adsorption seems to be ion exchange.